Computed tomography abbreviated assessment of sarcopenia following trauma: The CAAST measurement predicts 6-month mortality in older adult trauma patients. Issue 5 (May 2016) - Leeper, Christine M.; Lin, Elizabeth; Hoffman, Marcus; Fombona, Anisleidy; Zhou, Tianhua; Kutcher, Matthew; Rosengart, Matthew; Watson, Gregory; Billiar, Timothy; Peitzman, Andrew; Zuckerbraun, Brian; Sperry, Jason
Abstract : BACKGROUND: Older adult trauma patients are at increased risk of poor outcome, both immediately after injury and beyond hospital discharge. Identifying patients early in the hospital stay who are at increased risk of death after discharge can be challenging. METHODS: Retrospective analysis was performed using our trauma registry linked with the social security death index from 2010 to 2014. Age was categorized as 18 to 64 and 65 years or older. We calculated mortality rates by age category then selected elderly patients with mechanism of injury being a fall for further analysis. Computed Tomography Abbreviated Assessment of Sarcopenia for Trauma (CAAST) was obtained by measuring psoas muscle cross-sectional area adjusted for height and weight. Kaplan-Meier survival analysis was performed, and proportional hazards regression modeling was used to determine independent risk factors for in-hospital and out-of-hospital mortality. RESULTS: A total of 23, 622 patients were analyzed (16, 748, aged 18–64 years; and 6, 874, aged 65 or older). In-hospital mortality was 1.96% for ages 18 to 64 and 7.19% for age 65 or older ( p < 0.001); postdischarge 6-month mortality was 1.1% for ages 18 to 64 and 12.86% for age 65 or older ( p < 0.001). Predictors of in-hospital and postdischarge mortality for ages 18 to 64 and in-hospital mortality for ages 65 or older group included injury characteristics such as ISS, admission vitals, and head injury. Predictors of postdischarge mortality for age 65or older included skilled nursing before admission, disposition, and mechanism of injury being a fall. A total of 57.5% (n = 256) of older patients who sustained a fall met criteria for sarcopenia. Sarcopenia was the strongest predictor of out-of-hospital mortality in this cohort with a hazard ratio of 4.77 (95% confidence interval, 2.71–8.40; p < 0.001). CONCLUSION: Out of hospital does not assure out of danger for the elderly. Sarcopenia is a strong predictor of 6-month postdischarge mortality for older adults. The CAAST measurement is an efficient and inexpensive measure that can allow clinicians to target older trauma patients at risk of poor outcome for early intervention and/or palliative care services. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III.